Prevalence and Antibiotic Resistance Patterns of Bacteriuria in Patients Attending Bharatpur Hospital, Nepal - Kandel, Sagar; Sapkota, Kalyan (Journal of Bharatpur Hospital, 2025)
Background: Urinary tract infections (UTIs) are a major global health issue, causing significant morbidity. Early detection and effective treatment are crucial, but rising antibiotic resistance poses a challenge. This study investigates the prevalence of bacteriuria, demographic variations, and antimicrobial resistance patterns to guide better UTI management strategies. Methods: A cross sectional study was carried out among patient attending Bharatpur Hospital for a period of five months. A total of 1,111 midstream urine samples were analyzed. Bacterial isolates were identified, and their distribution was analyzed to evaluated the demographic variations in UTI prevalence and resistance pattern. Results: Among 1,111 urine samples, 693 (62.38%) were from females and 418 (37.62%) from males. Culture positivity was higher in females (76%) than males (24%), with sexually active women most affected (54.16%). E. coli (80.61%) was the predominant isolate, followed by K. pneumoniae (9.38%) and other less common bacteria. Antibiotic resistance was high, with E. coli (71.4%) and K. pneumoniae (85.7%) showing significant multidrug resistance (MDR). Nitrofurantoin was the most effective antibiotic, while cefixime and ciprofloxacin showed high resistance. Conclusions: Bacteriuria was more prevalent in females, with E. coli as the dominant uropathogen. High multidrug resistance, particularly to cefixime and ciprofloxacin, highlights the need for further research, regular surveillance, and effective antibiotic stewardship.